2012
DOI: 10.1007/s12639-012-0154-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and seasonal variation in ixodid ticks on cattle of Mathura district, Uttar Pradesh

Abstract: Considering the economic impact of various ticks species on livestock, the present study was conducted for epidemiological characterize of common ticks infesting Indian zebu cattle between July 2010 and June 2011 period at various locations of Mathura region of India. A total of 2,515 zebu cattle were examined on random basis throughout the year. The overall prevalence of ticks infestation in cattle was 60.07 %. The highest prevalence was reported in September (75 %) while the lowest was in January (46.07 %). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 5 publications
(6 reference statements)
8
22
2
Order By: Relevance
“…The genus has the ability to live in high temperature and humid areas (16). Iraq and more specifically the middle of Iraq, Al-Najaf, suffers very hot summers with temperatures could reach up to 120 °F (17).The current study results agree with (18) who found that genus Hyalomma was the most detected ticks in Iraq. The use of these external features to differentiate between tick genera is important to start the classification process of these Acari (19), however, more details of the species level are generated via studying the genetic components of these parasites (20).…”
Section: Discussionsupporting
confidence: 87%
“…The genus has the ability to live in high temperature and humid areas (16). Iraq and more specifically the middle of Iraq, Al-Najaf, suffers very hot summers with temperatures could reach up to 120 °F (17).The current study results agree with (18) who found that genus Hyalomma was the most detected ticks in Iraq. The use of these external features to differentiate between tick genera is important to start the classification process of these Acari (19), however, more details of the species level are generated via studying the genetic components of these parasites (20).…”
Section: Discussionsupporting
confidence: 87%
“…In current study, the obtained results showed that Boophilus tick was the only tick species infect cattle, these results were in agreement with Said and Atif (1958) in Shebin El-Kanatir district, Salem (1986) at Sidi Salem district, Darweesh (1999) in Elbehaira Province, El-Kammah et al, (2001) in Giza, Sharkia, Ismailia, El Beheira and Sinai who recorded Boophilus annulatus was found only on cows (100%), Patel et al, (2013) in India and Ramadan et al, (2016) Ramadan et al, (2016) in Qalyobia governorate and disagree with El-Housary (1981) at Kafr El-Sheikh and Ibrahim (1981) in El-Minyia, Rony et al, (2010) in Bangladesh. Mossie et al, (2016) in Ethiopia and Ali et al, (2016) in Pakistan.The difference may be due to use of acaricides and hygienic measures in different localities as well as the immune status of animals.…”
Section: -Discussionsupporting
confidence: 90%
“…in cattle were the neck and dewlap which in agreement with Tessema and Gashaw (2010) in Ethiopia, Ikpeze et al, (2011) in Nigeria, Patel et al, (2013) in India Wasihun and Doda (2013) and Gedilu et al, (2014) in Ethiopia While disagree with Hasson (2012) in Aldoura region south Baghdad, Ali et al, (2016) in Pakistan.The variation of tick species may be the cause associated with this matchlessness, as Boophilus spp. has short mouth part so prefer sites of thin-skinned and long hair.…”
Section: -Discussionsupporting
confidence: 60%
“…and mixed ticks in the targeted large animals ( Table 2). On the basis of finding of present and past study of Indian authors (Patel et al, 2013;Singh and Rath, 2013;Dehuri et al, 2017;Debbarma et al, 2017) the R. (B.)…”
Section: Resultsmentioning
confidence: 92%